PERBEDAAN JUMLAH LIMFOSIT PENGGUNA AIR SUNGAI MARTAPURA DENGAN PENGGUNA AIR PDAM BANDARMASIH - Eldha Savitri; Huldani Huldani; Rahmiati Rahmiati (Homeostasis, 2019)
Abstract: The amount of water pollution will affect the quality of the river water and affect its immunity. The government's effort to provide clean water is the existence of a regional water company. The aim of this research was to find out the differences of lymphocyte counts between Martapura River water consuments and Bandarmasih local water supply utility consuments for daily in Banjarmasin August 2018. This study was an analytic observational with cross sectional approach. A total of 60 samples have been selected by purposive sampling which is divided into 2 groups. The results showed that the average of lymphocyte counts of river water consuments was 34.8% and the average of lymphocyte counts of local water supply utility consuments was 32.8%. Analyzed the data used T - independent test showed that there were no significant differences of lymphocyte counts betweem Martapura River water consuments and Bandarmasih local water supply utility consuments in Banjarmasin August 2018 (p=0.318). Keywords: river water, local water supply utility, immunity, lymphocyte Abstrak: Pencemaran air akan mempengaruhi kualitas air sungai dan berdampak terhadap penggunanya yaitu imunitas. Program pemerintah dalam menyediakan air bersih ialah didirikannya perusahaan daerah air minum (PDAM). Penilitian ini bertujuan untuk mengetahui perbedaan jumlah limfosit pengguna air sungai Martapura dengan pengguna air PDAM Bandarmasih untuk keperluan sehari-hari di Kota Banjarmasin periode Agustus 2018. Penelitian ini bersifat observasional analitik dengan pendekatan cross sectional. Sebanyak 60 orang telah dipilih dengan metode purposive sampling yang terbagi menjadi 2 kelompok. Hasil penelitian menunjukkan rerata jumlah limfosit pengguna air sungai ialah 34.8% dan rerata jumlah limfosit pengguna air PDAM ialah 32.8%. Analisis data mengunakan uji T Test tidak berpasangan menunjukan tidak terdapat perbedaan yang bermakna antara jumlah limfosit pengguna air Sungai Martapura dan pengguna air PDAM Bandarmasih di Kota Banjarmasin periode Agustus 2018 (p=0,318). Kata-kata kunci: air sungai, air PDAM, imunitas, limfosit